The lessons learned from following evidence-based policy advocacy process in Vietnam and the Philippines - International Potato Center (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Vietnam and the Philippine are fast changing with strong economic growth, population increase and rapid urbanization. Along with other large Asian economies such as China, India, Indonesia, Thailand, and Malaysia, these two economies are expected to lead Asia’s advance to prosperity in the coming decade.